PENGARUH IKLIM ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DI SMA NEGERI 1 PARIANGAN - Renil Fortunately; Asmendri Asmendri; M. Haviz M. Haviz (al-fikrah: Jurnal Manajemen Pendidikan, 2019)
This study aimed to assess the effect of organizational climate on teacher performance, organizational culture on teacher performance and assess the effect of organizational climate and organizational culture together on the teacher performance in SMA Negeri 1 Pariangan. The sample of the study involved 48 teachers in SMA Negeri 1 Pariangan by using total sampling technique. The data were collected by using questionnaire. The findings revealed that (1) Organizational climate significantly influence the performance of teachers in SMA Negeri 1 Pariangan. (2) Organizational culture significant effect on the performance of teachers in SMA Negeri 1 Pariangan. (3) Organizational climates and organizational culture together significant effect on the performance of teachers in SMA Negeri 1 Pariangan.